Produção de Kombucha utilizando distintos tipos de açúcares e chás: caracterização molecular da microbiota e avaliação físico-química do processo fermentativo - Martins, Hevelynn Franco (2025)
Kombucha is a fermented beverage produced by the action of a symbiotic culture of bacteria and yeast on Camellia sinensis must and sugars, and is widely consumed due to its potential health benefits. However, the influence of different sugar sources on the fermentation process and on the microbiological, chemical and bioactive composition of the beverage still lacks systematic studies. Thus, this study aims to evaluate the effect of guarana syrups, honey and crystal sugar on the fermentation of Kombucha, analyzing their microbiological, physicochemical and bioactive characteristics, in addition to the economic predictions of microscale production. The tests were conducted according to a factorial design, with analysis of the microbiota by metabarcoding (Amplicon Sequence Variants and Operational Taxonomic Units), characterization of organic acids, phenolic compounds, fibers, antioxidant capacity and technological evaluation of patents. The results indicated that fermentation with guarana syrup presented higher consumption of glucose (64%) and fructose (64%), with accumulation of citric acid (1.60 g L⁻¹), tartaric acid (0.39 g L⁻¹) and alcohol (0.8%) after 12 days. Kombucha sweetened with honey accumulated acetic acid (16.93 g L⁻¹), lactic acid (0.14 g L⁻¹), total acidity (1.31 g.100mL⁻¹), volatile acidity (1.01 g.100mL⁻¹) and higher Scoby biomass, with maltose (21.87 g L⁻¹). The genus Komagataeibacter predominated in all samples, with variations in microbial diversity according to the type of tea and sweetener. The analysis of phenolic compounds revealed greater preservation of epicatechin gallate and epigallocatechin gallate in treatments with green tea, while honey modulated phenolic conversion. The antioxidant activity, evaluated by DPPH and FRAP methods, was higher in beverages prepared with green tea, suggesting greater stability of the bioactive compounds. The tests using black and green tea (50-50%) sweetened with honey and guarana syrup showed higher content of cellulose(2.42-2.55%), holocellulose (5.06-5.59%), hemicellulose (2.51-2.98%) and Klason insoluble lignin (4.05-4.58%). The patent analysis identified 365 registrations in Espacenet, with China leading (63%), and only 10 in INPI between 2017 and 2022, with a peak in 2020. The economic viability indicated a unit cost of R$ 4.77 per 500 mL bottle and a profit of 50% per unit sold. This study contributes to the valorization of regional raw materials and to the development of innovative functional products, adding knowledge to the fermented beverage sector.